Clinical Significance of Hemostatic Parameters in the Prediction for Type 2 Diabetes Mellitus and Diabetic Nephropathy. (4th February 2018) - Pan, Lianlian; Ye, Yali; Wo, Mingyi; Bao, Danni; Zhu, Fengjiao; Cheng, Maoliang; Ni, Xiuwen; Fei, Xianming
Abstract : It would be important to predict type 2 diabetes mellitus (T2DM) and diabetic nephropathy (DN). This study was aimed at evaluating the predicting significance of hemostatic parameters for T2DM and DN. Plasma coagulation and hematologic parameters before treatment were measured in 297 T2DM patients. The risk factors and their predicting power were evaluated. T2DM patients without complications exhibited significantly different activated partial thromboplastin time (aPTT), platelet (PLT), and D-dimer (D-D) levels compared with controls (P < 0.01 ). Fibrinogen (FIB), PLT, and D-D increased in DN patients compared with those without complications (P < 0.001 ). Both aPTT and PLT were the independent risk factors for T2DM (OR: 1.320 and 1.211, P < 0.01, resp.), and FIB and PLT were the independent risk factors for DN (OR: 1.611 and 1.194, P < 0.01, resp.). The area under ROC curve (AUC) of aPTT and PLT was 0.592 and 0.647, respectively, with low sensitivity in predicting T2DM. AUC of FIB was 0.874 with high sensitivity (85%) and specificity (76%) for DN, and that of PLT was 0.564, with sensitivity (60%) and specificity (89%) based on the cutoff values of 3.15 g/L and 245 × 10 9 /L, respectively. This study suggests that hemostatic parameters have a low predicting value for T2DM, whereas fibrinogen is a powerful predictor for DN.